Creating island resorts - King, Brian E. M. (Routledge advances in tourism, 2002)
This work studies tropical island resorts, the people who live and work there and the tourists who visit them. The author includes, but goes beyond the more commonly encountered marketing and economic analyses of resort destinations, by examining social, cultural, mythical, environmental, organizational and political dimensions.